Acute and Subchronic Toxicity of Forastero Cocoa from Côte d'Ivoire - KOUAME, Estelle-Clémence; KRA , Adou Koffi Mathieu; KOUASSI, Konan Armand Marcelin; GNAHOUE, Goueh; DJAMAN, Allico Joseph (European Journal of Applied Sciences, 2023)
In Côte d'Ivoire, forastero cocoa is used by traditional healers to treat metabolic and chronic diseases like diabetes. This study aims to assess the toxicity of extracts from forastero cocoa. Serial extraction was performed from cocoa powder using ethanol, distilled water and hexane. The phytochemical screening of aqueous and hydroethanolic extracts and crude cocoa powder was carried out using appropriate specific reagents. Acute and subchronic oral toxicity studies were performed in rats according to OECD guidelines 423 and 408. The phytochemical screening reveals the presence of polyterpenes, polyphenols, alkaloids and saponosides in the aqueous, hydroethanolic extracts and crude cocoa powder. Regarding acute toxicity, the LD50 value is higher than 5000 mg/kg body weight. In subchronic toxicity, results show that for all the doses there is a significant increase in the weight of male and female rats. Furthermore, no signs of intoxication or mortality were observed during 90 days. Analysis of hematological and biochemical parameters reveals that there is no significant change in blood parameters values and liver, kidneys and heart serum markers. On the whole, the results show that extracts from forastero cocoa are not toxic.